2014
DOI: 10.1002/adsc.201400363
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Michael/aza‐Michael/Cyclization Organocascade to Tetracyclic Spiroindolines: Concise Total Synthesis of Kopsinine and Aspidofractine

Abstract: The method succeeds for indole derivatives equipped with electron‐donating substituents on the benzene ring, but fails with the electron‐withdrawing fluoro‐substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 52 publications
0
23
0
1
Order By: Relevance
“…The Mannich‐type cyclization of one of the diastereoisomers would have to be faster than the other, resulting in a diastereomerically enriched product. Inspired by these results, we then tested a series of chiral phosphoric acids with the aim to explore a catalytic asymmetric process to assemble pentacyclic spiroindolines, which remains challenging, and few examples have so far been reported . After screening of reaction conditions, we found that the utilization of 15 mol % chiral phosphoric acid ( S )‐ CP10 in ClCH 2 CH 2 Cl at −10 °C or 0 °C was optimal to form 4 a with good yield (65 %) and moderate enantioselectivity (87:13 er; see the Supporting Information for details).…”
Section: Figurementioning
confidence: 99%
“…The Mannich‐type cyclization of one of the diastereoisomers would have to be faster than the other, resulting in a diastereomerically enriched product. Inspired by these results, we then tested a series of chiral phosphoric acids with the aim to explore a catalytic asymmetric process to assemble pentacyclic spiroindolines, which remains challenging, and few examples have so far been reported . After screening of reaction conditions, we found that the utilization of 15 mol % chiral phosphoric acid ( S )‐ CP10 in ClCH 2 CH 2 Cl at −10 °C or 0 °C was optimal to form 4 a with good yield (65 %) and moderate enantioselectivity (87:13 er; see the Supporting Information for details).…”
Section: Figurementioning
confidence: 99%
“…An enantioselective Michael/aza‐Michael/cyclization organocascade cascade annulation reaction was developed by Wu and co‐workers to access the core structures of Kopsia alkaloid in 2014 (Scheme ) . The annulation cascade was initiated with an organocatalytic Michael addition of tryptamine derivative to the propargyl aldehyde.…”
Section: Nucleophilic Additionsmentioning
confidence: 99%
“…[25] An enantioselective Michael/aza-Michael/cyclization organocascade cascade annulation reaction was developed by Wu and co-workerst oa ccess the core structures of Kopsia alkaloid in 2014 (Scheme 6). [26] The annulation cascade was initiated with an organocatalytic Michael addition of tryptamine derivative to the propargyl aldehyde. Then af ollowing aza-Michael additon of carbamate to the a,b-unsaturated iminium afforded aldehyde 54.A tl ast, the cyclization by the addition of the enamine to the aldehyde and spontaneousd ehydration and tautomerization would readily afford the tetracyclic indoline 55 in moderate to good yields (56-78 %) and excellent enantioselectivities (84-96 % ee).…”
Section: Nucleophilic Additionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] In this regard, great effort has been devoted to the development of enantioselective construction of these skeletons. [4,5] However,t he diastereoand enantioselective control usually suffers when the vicinal tertiary and all-carbon quaternary stereocenters are generated in the dearomatization process. [4,5] However,t he diastereoand enantioselective control usually suffers when the vicinal tertiary and all-carbon quaternary stereocenters are generated in the dearomatization process.…”
mentioning
confidence: 99%